Impact of disaggregated public expenditure on inflation rate in selected African countries: A panel cointegration analysis - Favour Chidinma Onuoha; George Okorie (West African Journal of Monetary and Economic Integration, 2020)
The study examined the long run association between disaggregated public expenditure and inflation rate in selected African countries with data spanning 1990-2019. The study employed a panel cointegration technique and estimated the cointegrating relationship using the Fully Modified OLS (FMOLS), and Dynamic OLS (DOLS) proposed and advanced by Pedroni (1996, 2001) and Kao and Chiang (2001). The findings from the cointegration result reveal the existence of a long run equilibrium relationship among the variables. Also, the panel dynamic OLS revealed that a 1percent change in infrastructure (capital) and defense expenditures leads to about 0.56 percent and 0.27 percent incremental change in inflation rate respectively. On the other hand, expenditure on education has a positive and an insignificant relationship with inflation, while expenditure on health has an inverse but insignificant influence on inflation rate in the region within the period under study. The study recommends that public expenditure on infrastructure in the selected African countries be appropriately channeled to stimulate investment and production, thereby stabilizing prices.
Keywords: H55; H54; H57; E31; C33; 330; Health; Infrastructure; Defense; Inflation; PFMOLS; PDOLS